The general natural logarithmic function [tex]y=ln(x)[/tex] has an asymptote at [tex]x=0[/tex]. To make this function have an asymptote at [tex]x=-1[/tex], we need to translate the function 1 unit left. So the new function (according to rules of translations) takes the form
[tex]y=ln(x+1)[/tex]
This function should also go through two points [tex](0,0)[/tex] and [tex](2,1)[/tex]. Let's check (0,0).
[tex]ln(0+1)=ln(1)=0[/tex]. So the first point is okay. Let's check (2,1).
[tex]ln(2+1)=ln3[/tex], which is not equal to 1.
A simple trick to make this equal to 1, for us to satisfy all the conditions of making this function, is to think "What can we do to [tex]ln(3)[/tex] to make it equal to 1?"
Simple! We have to multiply it by [tex]\frac{1}{ln(3)}[/tex]!
Now, our final equation becomes [tex]y=\frac{1}{ln(3)}ln(x+1)[/tex].
ANSWER: [tex]y=f(x)=\frac{1}{ln(3)}ln(x+1)[/tex]